PEMANTAPAN CAREGIVER DALAM PELAYANAN KOMPLEMENTER PADA GERIATRI (PENDAMPINGAN SMK PUSAT KEJURUAN) - Ulfa, Ana Farida; Pujiani, Pujiani; Zuliani, Zuliani; Rhamandani, Widiyanto; Prihartini, Endang Suhartatik; Liala, Haniah Nur (PPM STIKES Adi Husada, 2024)
Introduction & Aim: Vocational High School (SMK) is a secondary education level organized to prepare graduates to enter the world of work. Vocational School's flagship program is to make graduates professional, ready, and skilled to synergize with the world of work, and are nursing assistants with specialization skills as caregivers. This community service activity aimed to strengthen alumni as caregivers through the Strengthening Caregivers in Complementary Services for Geriatric workshop. Method of Activity: the method of this community service activity is Participatory Action Research (PAR) with the form of activities What was carried out was a lecture and discussion on the topic of geriatric care and complementary cupping therapy, the activity continued with a simulation of the SOP for implementing cupping therapy and participant participation in cupping therapy activities at community service activities. about therapy in geriatrics and cupping training. The activity continued by involving students in cupping nursing therapy community service activities. Results: The community service activities of workshops, seminars, and complementary cupping therapy training ran smoothly, and were very relevant to the needs of SMK PK Bakti Indonesia Media alumni in providing services to the elderly. Discussion: Cupping therapy is relevant to the competency of vocational school graduates in providing services (caregivers) to the elderly. This is in accordance with the characteristics of Indonesian society, which is predominantly Muslim. Based on the results of community service activities, it was found that cupping therapy is effective for elderly people with hypertension, rheumatoid arthritis, gout, and bone pain. Cupping therapy competency can improve the quality of teaching factory implementation in vocational schools.